P-glycoprotein Inhibition for Optimal Drug Delivery - Md. Lutful Amin (AboutScience Srl, 2013)
P-glycoprotein (P-gp), an efflux membrane transporter, is widely distributed throughout the body and is responsible for limiting cellular uptake and the distribution of xenobiotics and toxic substances. Hundreds of structurally diverse therapeutic agents are substrates to it and it impedes the absorption, permeability, and retention of the drugs, extruding them out of the cells. It is overexpressed in cancer cells and accountable for obstructing cell internalization of chemotherapeutic agents and for developing transporter mediated resistance by cancer cells during anti-tumor treatments. As it jeopardizes the success of drug delivery and cancer targeting, strategies are being developed to overcome P-gp mediated drug transport. This concise review represents a brief discussion on P-gp mediated drug transport and how it hinders the success of various therapies. Its main focus is on various strategies used to tackle this curb in the field of drug delivery and targeting.